2008
DOI: 10.1021/bp050057v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetylcystein on Butyrate-Treated Chinese Hamster Ovary Cells To Improve the Production of Recombinant Human Interferon-β-1a

Abstract: Sodium butyrate (NaBu) is used as a productivity enhancer for the production of therapeutic recombinant proteins in Chinese hamster ovary (CHO) cells. However, NaBu is well-known for having a cytotoxic effect, thereby inducing apoptosis. As an endeavor to reduce this defect, we studied 11 antioxidants known for inhibiting apoptosis, according to a Plackett-Burman statistical design on CHO cells producing recombinant interferon-beta-1a (IFN-beta). None of the antioxidants that we tested were as effective as N-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 51 publications
4
24
0
Order By: Relevance
“…Cell arrest obtained by hypothermia or addition of a chemical, e.g. butyrate, has been reported for perfusion; given that the cell specific productivity is comparable or increased and that the protein quality is correct or improved (Ducommun et al 2002a;Chotteau et al 2001;Chen et al 2004;Kim et al 2004;Angepat et al 2005;Oh et al 2005;Meuwly et al 2006;Ahn et al 2008;Zhang et al 2014a). Another advantage of lowering the temperature under 35.5 C is that the proteolytic activity is lower compared to 37 C (Chuppa et al 1997).…”
Section: Cell Arrestmentioning
confidence: 99%
“…Cell arrest obtained by hypothermia or addition of a chemical, e.g. butyrate, has been reported for perfusion; given that the cell specific productivity is comparable or increased and that the protein quality is correct or improved (Ducommun et al 2002a;Chotteau et al 2001;Chen et al 2004;Kim et al 2004;Angepat et al 2005;Oh et al 2005;Meuwly et al 2006;Ahn et al 2008;Zhang et al 2014a). Another advantage of lowering the temperature under 35.5 C is that the proteolytic activity is lower compared to 37 C (Chuppa et al 1997).…”
Section: Cell Arrestmentioning
confidence: 99%
“…Process parameters such as pH, temperature and dissolved oxygen tension (DOT) have been shown to exert a significant effect on cell line performance. In contrast to reports where improvements in process performance have been achieved by the addition of nutrient supplements (Oh et al, 2005;Sung et al, 2004) or by means of metabolic or genetic engineering (Fussenegger and Betenbaugh, 2002), the improvement of process performance by simple parameter optimization offers a cheap and valuable strategy for process optimization. In this context, the pH is a parameter known to significantly influence cell growth, recombinant protein production, cell metabolism and protein glycosylation (Borys et al, 1993;Kurano et al, 1990;Link et al, 2004;Miller et al, 2000;Yoon et al, 2005;Zanghi et al, 1999b).…”
Section: Introductionmentioning
confidence: 98%
“…It was reported that the addition of, e.g., DMSO, glycerol, or sodium butyrate can enhance the production of biopharmaceuticals in different mammalian cells (Liu and Chen 2007;Oh et al 2005;Rodriguez et al 2005;Cherlet and Marc 2000). Despite an increase in specific productivity in many producers, treatment with these chemicals results usually in a reduced growth rate that can reduce the final product titer compared to untreated cells (Rodriguez et al 2005).…”
Section: Introductionmentioning
confidence: 99%